Legal Protection for Legislative Candidat Members Based Onlaw No. 7 of 2023 Concerning General Elections at The KPU of Deli Serdang District - Fadri, Muhammad; Harahap, Herlina Hanum (Jurnal Smart Hukum (JSH), 2026)
The objectives of this research are for knowing how to implement Law No. 7 of 2017, To find out the efforts that have been made to recruit legislative candidates in accordance with Law No. 7 of 2017, To find out whether the considerations of Law No. 7 of 2017 are appropriate for prospective legislative candidate. This research is a qualitative research with a descriptive-qualitative approach. In this study, after the researcher collects data in the form of interview results, documentation, and observations, the data will then be analyzed in more depth so as to form a scientific-natural conclusion that can be accepted by various groups, especially in this case the Deli Serdang Police itself as the object of research in this thesis and community leaders.